Islamic Education in Indonesia: Civilization and the Development of National Character - Aisyah, Aisyah; Ismail , Fajri; Zuhdiyah, Zuhdiyah; Ismail, Ismail (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islamic education in Indonesia has long been an integral part of the national education system, with institutions such as pesantren and madrasah not only teaching religious knowledge but also nurturing the intellectual and moral potential of students. This form of education plays a significant role in shaping a nation of noble character capable of living harmoniously amidst social diversity. This study employs a qualitative method. The findings indicate that Islamic education in Indonesia plays a crucial role in the nation's civilizational development through its long-standing history, contributing to the formation of fundamental religious, moral, and social values within society. It not only strengthens Islamic identity but also supports the advancement of science and culture unique to Indonesia. In the modern era, Islamic education serves as a key foundation for character development by integrating spiritual, ethical, and moral values into an adaptive and innovative learning process. This transformation is essential for addressing global challenges and shaping a generation that is not only academically competent but also possesses strong character, inclusivity, and a readiness to contribute to sustainable national development.